2013
DOI: 10.1123/jsm.27.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Do Charity Sport Events Function as “Brandfests” in the Development of Brand Community?

Abstract: Given the ubiquity of charitable organizations and the events used to solicit donations for a cause, many charity-based organizations are continually looking for ways to expand their fundraising efforts. In this quest, many have added endurance sport events to their fundraising portfolios. Anecdotally, we know that building long-term and meaningful relationships with current (and potential) donors is critical for a nonprofit organization’s success. However, there is a paucity of research regarding whether thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 29 publications
(58 reference statements)
6
58
0
Order By: Relevance
“…The work that adapts affinity and loyalty concepts from the realm of relationship marketing as applied in industry can be instructive. In particular, we see research associated with building and sustaining brand communities that has had success in industry (cf Algesheimer, Dholakia, & Herrmann, 2005;McAlexander, Schouten, & Koenig, 2002;Muniz & O'Guinn, 2001), showing promise for institutional development (cf Hassay & Peloza, 2009;McAlexander, Koenig, and Schouten, 2006;Miller, 2009;O'Sullivan, 2009;Woolf, Heere, & Walker, 2013). This contemporary research empirically measures alumni affinity as it relates to how the university's graduates assess the value of their degrees, their feelings about the institution's identity, their relationships with the institution's representatives (e.g.…”
Section: Affinity and Givingmentioning
confidence: 95%
“…The work that adapts affinity and loyalty concepts from the realm of relationship marketing as applied in industry can be instructive. In particular, we see research associated with building and sustaining brand communities that has had success in industry (cf Algesheimer, Dholakia, & Herrmann, 2005;McAlexander, Schouten, & Koenig, 2002;Muniz & O'Guinn, 2001), showing promise for institutional development (cf Hassay & Peloza, 2009;McAlexander, Koenig, and Schouten, 2006;Miller, 2009;O'Sullivan, 2009;Woolf, Heere, & Walker, 2013). This contemporary research empirically measures alumni affinity as it relates to how the university's graduates assess the value of their degrees, their feelings about the institution's identity, their relationships with the institution's representatives (e.g.…”
Section: Affinity and Givingmentioning
confidence: 95%
“…Research into online brand communities has examined how to utilise them in product development (Kim and Bae, 2008); promote consumer participation (Casaló et al, 2008), and how consumers engage with the community (Lee et al, 2011;, Brodie et al, 2013;Baldus et al, 2015). Within sport, extensive empirical work has been carried out into brand communities, focusing on team and other group identities (Heere and James, 2007;Heere et al, 2011a;Heere et al, 2011b), new sport teams (Grant et al, 2011), brandfests (Woolf et al, 2013) and scale-free networks within a new brand community (Katz andHeere, 2013, 2015). A recent study by Yoshida et al (2015a) found that "fan community attachment is the only construct that can predict attendance frequency over a longer period of time", and a further study by Yoshida et al (2015b) found that "fan community identification had positive effects on team brand equity and […] fan community engagement, customized product use, member responsibility, and positive word-of-mouth".…”
Section: Sports Marketing Community and Consumptionmentioning
confidence: 99%
“…Participants interact with sponsors through the event as well as the event's association with the charity/cause (Woolf, Heere, & Walker, 2013). Sponsors may have a direct link to the event, producing a high level of sponsor event congruence for participants.…”
Section: Linking the Charitable Eventmentioning
confidence: 99%
“…Several studies have examined participant motivations for participating in charity-affiliated sporting events and involvement or identification with the charity (Bennett et al, 2007, Woolf et al, 2013. Filo et al (2007Filo et al ( , 2009Filo et al ( , 2010Filo et al ( , 2011 offer a series of studies examining participant motives for charitable giving, intention to purchase from the sponsor, and repeat attendance at fund raisers.…”
Section: Attitudes Toward the Charity Or Causementioning
confidence: 99%
See 1 more Smart Citation